Our Opium Wars: The Ghosts of Empire in the Prescription Opioid Nightmare. Issue 5 (2nd November 2018) - Haiven, Max
Abstract: The prescription opioid crisis in the United States is among the worst human-caused public health disasters in modern history, with over 500, 000 dead and by some estimates almost 5% of the American population 'misusing' these drugs. This article supplies some unusual resources for understanding that crisis and the way it inherits a legacy of empire, now transfigured for a corporate age. From the museums funded by the sale of these drugs to the British-led Opium Wars to the present-day racialised dimensions of the epidemic, much can be gained from dwelling with its tangled and haunted complexities. The article concludes with a consideration of Susan Buck-Morss's reading of Walter Benjamin's meditations on the aestheticisation of politics in an age of what she calls capitalist anaesthetics.